Examining Marketing Mix Strategy on Consumer Intention To Buy: Empirical Study on Alfa Mart Retail Store at Manado City - Juliana Ohy (Journal of International Conference Proceedings (JICP), 2018)
Retail store at Manado city from year 1990 to 2017 facing fascinating development. The competition between them obviously forced to make excellent strategy. Cutting price, interesting layout, excellent and unique services are the examples of marketing strategy could conduct by retail store. The successful retail store has to fulfill the need of consumer such as served with high quality product, compete price, services and other promotion. Meanwhile, location and another facilities retail store has also to be aware. Unsatisfied consumer will make negative effect on moving consumer to other store who served better services. If the situation continues the store will facing decreasing sales and profit. Hence, to prevent that loss, retail store has to create loyal consumer. This research tried to examine marketing mix on consumer intention to buy at Alfa Mart at Manado City. The analysis data used path analysis. The respondent is Alfa mart consumer, reached by accidental sampling. The number of samples is 161 data. The result of study was all the marketing mix variable such as product, price, place and promotion significant influenced on consumer intention to buy. Keywords: marketing mix, competition, intention to buy, retail store, Alfa Mart.